The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1017/s136898002200249x
|View full text |Cite
|
Sign up to set email alerts
|

Salt intake reduction using umami substance-incorporated food: a secondary analysis of NHANES 2017–2018 data

Abstract: Objective: Excessive salt intake raises blood pressure and increases the risk of non-communicable diseases (NCDs), such as cardiovascular disease, chronic kidney disease, and stomach cancer. Reducing the sodium content of food is an important public health measure to control the NCDs. This study quantifies the amount of salt reduced by using umami substances, i.e., glutamate, inosinate, and guanylate, for adults in the United States (US). Design: The secondary data analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Taken together, these data support current international recommendations of dietary salt restriction in individuals with diabetes with or without hypertension or evidence of kidney disease [9 & ,10]. The National Health and Nutrition Examination Survey (NHANES) suggested that umami substances as a substitute for salt, that is, glutamate, inosinate and guanylate, may help reduce the United States adults' salt intake by up to 13% [28]. Salt substitutes, usually contain potassium chloride, has emerged as a potentially attractive mechanism for reducing sodium intake.…”
Section: Salt-restricted Dietsupporting
confidence: 77%
See 1 more Smart Citation
“…Taken together, these data support current international recommendations of dietary salt restriction in individuals with diabetes with or without hypertension or evidence of kidney disease [9 & ,10]. The National Health and Nutrition Examination Survey (NHANES) suggested that umami substances as a substitute for salt, that is, glutamate, inosinate and guanylate, may help reduce the United States adults' salt intake by up to 13% [28]. Salt substitutes, usually contain potassium chloride, has emerged as a potentially attractive mechanism for reducing sodium intake.…”
Section: Salt-restricted Dietsupporting
confidence: 77%
“…The National Health and Nutrition Examination Survey (NHANES) suggested that umami substances as a substitute for salt, that is, glutamate, inosinate and guanylate, may help reduce the United States adults’ salt intake by up to 13% [28]. Salt substitutes, usually contain potassium chloride, has emerged as a potentially attractive mechanism for reducing sodium intake.…”
Section: Salt-restricted Dietmentioning
confidence: 99%